2015
DOI: 10.1088/0957-4484/26/25/255706
|View full text |Cite
|
Sign up to set email alerts
|

Silver catalyzed gallium phosphide nanowires integrated on silicon andin situAg-alloying induced bandgap transition

Abstract: In this work, we demonstrate a silver catalyzed heteroepitaxial growth of gallium phosphide nanowires (GaP NWs) on silicon. The morphology and growth direction of GaP NWs on differently orientated Si substrates were investigated. From crystallographic analysis, we inferred that Ag from catalyst is incorporated into the GaP during the chemical beam epitaxy (CBE) process. Using the PL spectrum and time-resolved emission spectroscopy, the optical properties of Ag-catalyzed GaP NWs were greatly modified, with band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Recently, Ag has emerged as a promising seed material for III-V semiconductor NW growth and may offer some benefits compared to Au [11][12][13][14]. Reports also suggest that another option is to engineer alloy NPs composed of two metals [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ag has emerged as a promising seed material for III-V semiconductor NW growth and may offer some benefits compared to Au [11][12][13][14]. Reports also suggest that another option is to engineer alloy NPs composed of two metals [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that Ag nanoparticles can be used to nucleate and grow NWs of InP, 52 InSb, 53 InAs, 54 and GaP. 55 Although these reports show varied yield and control of important NW properties (here meaning crystal phase and growth direction), they do suggest Ag as an interesting candidate for particle-seeded synthesis of III–V NWs in general for all of the commonly used epitaxy systems (i.e., metal–organic chemical vapor deposition/metal–organic vapor phase epitaxy, chemical beam epitaxy, and MBE). We find that GaAs NWs can indeed be grown using Ag as seed material, potentially offering some important benefits compared to Au.…”
mentioning
confidence: 99%
“…We have achieved NWs with non‐tapered morphology and uniform composition along the length by growth parameter optimization. AgNPs have also been used for growing NWs of InP, GaAs, GaP, InSb, and InAs . In a recent report, Lindberg et al demonstrated that Ag seeded growth of GaAs NWs and observed the growth of vertically aligned NWs on GaAs (100) surface.…”
Section: Introductionmentioning
confidence: 99%